Gravity wave activity in the mesopause region from airglow measurements at El Leoncito - Reisin, Esteban Rodolfo (2004)
Based on almost 1000 nights of OH(6-2) and O2b(0-1) airglow data measured during 1998–2002 at El Leoncito (31:8◦S, 69:2◦W), seasonal variations of gravity wave activity are determined from temperature and intensity variances. The photon-counting technique used permits to derive the individual statistical errors a priori, and to quantitatively isolate the geophysical variance. The two airglow emissions yield results for the altitudes of 87 and 95 km. Tidal activity contains most of the variance (especially between March and October) and therefore must be suppressed to obtain gravity wave activity. There are strong night-to-night variations, from completely quiet to variances of more than 80 K2 in temperature. The interannual variability was small enough to de;ne a meaningful seasonal climatology. The wave activity variation is semiannual, similar to previous radar wind results, including those at the same latitude, and has its main maximum in southern winter and a weaker maximum in summer. The growth of wave activity from 87 to 95 km, when interpreted in terms of an amplitude growth factor, leads to a value of 1:35 ± 0:01, similar to the one obtained for tides, in a previous paper of ours. From the comparison of intensity and temperature variance for a given emission, mean values of Krassovsky’s are derived (5:60 ± 0:09 for OH, and 5:08 ± 0:08 for O2), that compare favourably with results obtained from individual wave signatures. This proves the consistency between the wave activities derived from intensities and temperatures.